TENDENCIES OF COMPOSITIONAL CREATIVITY IN NEW UZBEKISTAN (Web of Technology: Multidimensional Research Journal, 2026)
This scientific article is devoted to the study of modern trends in the field of trends in the field of compositional creativity in Uzbekistan and notes the economic and social changes in the framework of the country's "strategy for the dissolution of New Uzbekistan" for 2022-2026.